Investigating Groundwater Quality in the Flood Prone Neighborhood Area in Malaysia - Nasir Nayan; Yazid Saleh; Mohmadisa Hashim; Hanifah Mahat; Koh Liew See (Indonesian Journal of Geography, 2019)
The purpose of this study is to compare the quality of groundwater during wet and dry seasons in Malaysia especially in Kuala Krai District which frequently involved in annual monsoon floods and the question whether the wells can be used during floods as well as an alternative source when there are no floods. Six sampling stations were selected using six main parameters which included DO, pH, BOD, COD, TSS and NH3N. The assessment was conducted based on the standards set by Malaysian INWQS and the classification of WQI. The results of the analysis showed that most of the water samples taken during the wet season had concentration values that did not meet the DOE standards such as the DO, BOD, and NH3N parameters. Based on the WQI classification, majority stations during the wet season were in moderately contaminated except for station T6 which was clean. On the contrary, during a dry season were found to be clean except for station T1 which was moderately contaminated.